Association of CFH and CFB Gene Polymorphisms with Retinopathy in Type 2 Diabetic Patients - Jun Wang; Ming Ming Yang; Yan Bo Li; Guo Dong Liu; Yan Teng; Xiao Min Liu (Mediators of Inflammation)
Objectives. The complement system is a key component of innate immunity and has been implicated in the pathogenesis of diabetic retinopathy (DR). This study aimed at investigating whether polymorphisms of two genes in the complement pathway, complement factor H (CFH) and complement factor B (CFB), are associated with DR. Methods. 552 well-defined subjects with type 2 diabetes, consisting of 277 DR patients and 275 diabetic controls, were recruited. Four Tag-SNPs rs1048709, rs537160, rs4151657, and rs2072633 in CFB and rs800292 (I62V) in CFH were examined using TaqMan Genotyping Assays. Results. There were significant increases in the frequencies of A allele and AA genotype for rs1048709 in DR patients compared with diabetic controls (Pcorr=0.035, OR=1.42; Pcorr=0.02, OR=2.27, resp.): meanwhile, significant decreases in the frequencies of A allele and AA genotype for rs800292 were observed in DR patients compared with diabetic controls (Pcorr=0.04, OR=0.72; Pcorr=0.015, OR=0.51, resp.). Joint effect of these two loci was also identified. Moreover, rs800292/AA genotype was found to be related with delayed progression to DR. Conclusions. CFH-rs800292 and CFB-rs1048709 are associated with the presence of DR, which strengthens the concept that complement system plays an important role in the pathogenesis of DR.